Gambaran Histopatologi Hepatopankreas Kepiting Bakau (Scylla serrata) di Kawasan Estuari Alue Naga, Banda Aceh Indonesia - Dedi Fazriansyah Putra; Nurul Fajar; Cut Dahlia Iskandar (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
The study aimed to investigate the histopathology status of the hepatopancreas of mangrove crabs (Scylla serrata) in the Alue Naga estuary area, Banda Aceh, Indonesia. The research was conducted in September and October 2020. The purposive sampling method was used where the determination of the location was based on water conditions and anthropogenic activities near the estuary. The mangrove crabs (Scylla serrata) sampling location was implemented within three sampling sites in the Krueng Cut estuary, Gampong Alue Naga, Syiah Kuala District, Banda Aceh. Histopathological analysis was carried out in the histology laboratory, Syiah Kuala University. The results showed that there were changes in the hepatopancreas in the form of irregular lumen star shape, the formation of vacuoles and basophilic hypertrophy. These hepatopancreas changes were assumed due to water pollution generated by anthropogenic activities from local settlements and household industries. Therefore, it is suggested to conduct further research regarding water quality parameters and heavy metal concentration within this sampling area.